A Frame Work for Decimal Floating Point Multiplier Using Vinculum Multipliers - Sreelakshmi, G.; Fatima, Kaleem; Madhavi, B. K. (New Insights into Physical Science Vol. 13, 2021)
IEEE Decimal floating point format play an important role in many financial, tax, account, commercial and internet based applications for which binary floating point format is not suitable. IEEE Standards Association approved a revision to the IEEE 754-1995 format to IEEE 754-2008 which includes specifications for DFP formats and operations. This paper broadens our past work on floating point multiplier utilizing proficient vinculum multipliers for mantissa multiplication and vinculum adders for adding exponents.